The Edinburgh Companion to the Short Story in English - Delaney, Paul 1972- (Edinburgh Companions to Literature and the Humanities, 2022)
New scholarly essays on the short story in English as a phenomenon of world literatureThis collection explores the history and development of the anglophone short story since the beginning of the nineteenth century. Ranging across texts from different parts of the English-speaking world, it studies the form in its many guises and venues of publication. Why have writers of so many nationalities and dispositions found the short story amenable to experimentation and discovery? What is the history and origin of the modern short story, and what has been the role of the publishing business, of academic criticism, of the Creative Writing 'industry', and of the digital revolution in shaping and disseminating it over the past two centuries? This collection of innovative essays by new and established scholars explores these and other questions, addressing stories from around the world, and considering their relationship to place, identity, history and genre.Key Features:New critical perspectives on the English-language short story by established scholars and new voicesProvides an international perspective on the formShowcases a wide range of critical approaches and perspectives, including Book History, genre criticism, postcolonial theory, queer studies, feminist criticism, war writing, disability studies, Creative Writing, and ecocriticism